What is the sum of all distinct values of c such that there exists positive integers a , b and c satisfying
a + 3 1 + b + 3 1 = 3 1 + c + 3 1
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Without loss of generality, we may assume that a ≤ b . Clearly RHS > 3 1 , thus LHS > 3 1 . If a = 3 , then b ≥ 3 and 6 1 + b + 3 1 ≤ 3 1 . Hence a = 1 or a = 2 .
Case 1: a = 1 . b + 3 1 1 2 ( c + 3 ) b c + 1 5 b − 9 c + 9 ( b − 9 ) ( c + 1 5 ) = 1 2 1 + c + 3 1 = ( b + 3 ) ( c + 3 ) + 1 2 ( b + 3 ) = 0 = − 1 4 4 = − 1 2 2
Since c + 1 5 > 0 thus we must have b − 9 < 0 , but b ≥ a = 1 so b − 9 ≥ − 8 . Hence we have ( b , c ) = ( 1 , 3 ) , ( 3 , 9 ) , ( 5 , 2 1 ) , ( 6 , 3 3 ) , ( 7 , 5 7 ) and ( 8 , 1 2 9 ) as solutions.
Case 2: a = 2 . b + 3 1 1 5 ( c + 3 ) 0 0 ( 2 b − 9 ) ( 2 c + 2 1 ) = 1 5 2 + c + 3 1 = 2 ( b + 3 ) ( c + 3 ) + 1 5 ( b + 3 ) = 2 b c + 2 1 b − 9 c + 1 8 = 4 b c + 4 2 b − 1 8 c + 3 6 = − 2 2 5 = − 3 2 × 5 2
Since 2 c + 2 1 > 0 , we must have 2 b − 9 < 0 . But b ≥ a = 2 , so 2 b − 9 ≥ − 5 . Hence 2 b − 9 = − 5 , − 3 , − 1 . This leads to corresponding solutions ( b , c ) = ( 2 , 1 2 ) , ( 3 , 2 7 ) and ( 4 , 1 0 2 ) .
Hence, the sum of all possible values of c are 3 + 9 + 2 1 + 3 3 + 5 7 + 1 2 9 + 1 2 + 2 7 + 1 0 2 = 3 9 3 .
L e t a + 3 = A , b + 3 = B , c + 3 = C j u s t t o m a k e t h e e q u a t i o n s l o o k n e a t . a + 3 1 + b + 3 1 = 3 1 + c + 3 1 b e c o m e s A 1 + B 1 = 3 1 + C 1 C = A 1 + B 1 − 3 1 1 C = 3 ( A + B ) − A B 3 A B T o s a t i s f y t h e g i v e n c o n d i t i o n s , 1 . A ≥ 4 ( S i n c e a ≥ 1 ) 2 . B ≥ 4 ( S i n c e b ≥ 1 ) A n d t h e d e n o m i n a t o r h a s t o b e p o s i t i v e , i . e , 3 ( A + B ) − A B > 0 o r 3 . 3 ( A + B ) > A B U s i n g t h e a b o v e c o n d i t i o n s w e c a n a s s i g n A a n d B c e r t a i n v a l u e s t o s e e w h i c h a l l s a t i s f y t h e c o n d i t i o n s . A n d s i n c e t h e e q u a t i o n i s s y m m e t r i c w . r . t A a n d B , w e c a n k e e p A c o n s t a n t a n d v a r y t h e o t h e r s u c h t h a t B ≥ A . C a s e 1 : A = 4 . W e s e e t h e o n l y v a l u e s o f B ≥ A t h a t s a t i s f y t h e c o n d i t i o n 3 a n d 2 a r e : B = 4 , 5 , 6 , 7 , 8 , 9 , 1 0 , 1 1 C a s e 2 : A = 5 . W e s e e t h e o n l y v a l u e s o f B ≥ A t h a t s a t i s f y t h e c o n d i t i o n 3 a n d 2 a r e : B = 5 , 6 , 7 C a s e 3 : A = 6 N o v a l u e s o f B ≥ A s a t i s f y t h e g i v e c o n d i t i o n s . L a s t c o n d i t i o n : C = I n t e g e r . T o s e e t h e v a l u e s o f A a n d B t h a t s a t i s f y t h a t , I j u s t p l u g i n t h e v a l u e s a n d d i s c a r d t h e v a l u e s t h a t d o n ′ t s a t i s f y . W e f i n d o u t , C = 6 , 1 2 , 2 4 , 3 6 , 6 0 , 1 3 2 , 1 5 , 3 0 , 1 0 5 S i n c e C = c + 3 , c = C − 3 c = 3 , 9 , 2 1 , 3 3 , 5 7 , 1 2 9 , 1 2 , 2 7 , 1 0 2 S u m m i n g t h e m u p , A n s w e r = 3 9 3
Problem Loading...
Note Loading...
Set Loading...
Without loss of generality, we may assume that a ≥ b . Note that as c is positive, we have 3 1 < 3 1 + c + 3 1 = a + 3 1 + b + 3 1 ≤ b + 3 2 . This implies that b + 3 < 6 ⇒ b < 3 . We split into cases, depending on the value of b .
Case 1: b = 1 . The original equation becomes a + 3 1 + 4 1 + 3 1 + c + 3 1 , which is equivalent to 1 2 1 + c + 3 1 − a + 3 1 = 0 . Cross multiplying, we obtain ( a + 3 ) ( c + 3 ) + 1 2 ( a + 3 ) − 1 2 ( c + 3 ) = 0 . We 'complete the factorization' by subtracting 144 on both sides to obtain ( a − 9 ) ( c + 1 5 ) = − 1 4 4 . Since a and c are positive integers, so c + 1 5 > 0 which implies that a − 9 < 0 , thus a < 9 .
We check all the possible values of 1 ≤ a ≤ 9 , to get that the solutions are ( a , c ) = ( 1 , 3 ) , ( 3 , 9 ) , ( 5 , 2 1 ) , ( 6 , 3 3 ) , ( 7 , 5 7 ) , ( 8 , 1 2 9 ) .
Case 2: b = 2 . The original equation becomes a + 3 1 + 5 1 = 3 1 + c + 3 1 . Similar as above, we cross multiply to obtain 2 ( a + 3 ) ( c + 3 ) + 1 5 ( a + 3 ) − 1 5 ( c + 3 ) = 0 . This is harder to factorize using the previous trick directly, but we multiply by 2 and subtract 225 to obtain ( 2 a − 9 ) ( 2 c + 2 1 ) = − 2 2 5 . Likewise, since a and c are positive integers, so 2 c + 2 1 > 0 ⇒ 2 a − 9 < 0 ⇒ a < 4 . 5 .
We check all the possible values of 1 ≤ a ≤ 4 to get that the solutions are ( a , c ) = ( 2 , 1 2 ) , ( 3 , 2 7 ) , ( 4 , 1 0 2 ) .
Hence, the sum of all possible values of c are 3 + 9 + 2 1 + 3 3 + 5 7 + 1 2 9 + 1 2 + 2 7 + 1 0 2 = 3 9 3 .